Product and Service Quality Towards Customer Satisfaction Refilled Drinking Water in Indonesia - Bakhtiar Tijjang; Nurfadhilah Nurfadhilah; Pandi Putra (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2020)
The quality of clean water is very crucial needed in human life to meet daily needs. According to the Ministry of Health, drinking water ready for consumption meets tasteless requirements, doesn't smell, is colorless, and contains heavy metals. Although humans can drink water from natural sources, it is risky to be contaminated by bacteria or other invisible harmful substances. The need for clean drinking water, consumable water provides business opportunities, one of them is refill drinking water. This study aims to examine product service quality to consumer satisfaction towards the refill drinking water in Indonesia. The type of research using the explanatory research approach (research explanation) uses a quantitative approach. The population in this study were customers of the refill drinking water in Indonesia whose population was unknown that using Roscoe method to take the sample, which are 50 people with incidental sampling technique. The results showed that product and service quality positively and significantly affect consumer satisfaction partially or simultaneously for customers to refill drinking water in Indonesia.